The Colombia Reader : History, Culture, Politics - Gómez López, Ana María, 1981-; Palacios, Marco; Farnsworth-Alvear, Ann, 1965- (Book collections on Project MUSE., 2017)
Containing over one hundred selections-most of them published in English for the first time-The Colombia Reader presents a rich and multilayered account of this complex nation from the colonial era to the present. The collection includes journalistic reports, songs, artwork, poetry, oral histories, government documents, and scholarship to illustrate the changing ways Colombians from all walks of life have made and understood their own history. Comprehensive in scope, it covers regional differences; religion, art, and culture; the urban/rural divide; patterns of racial, economic, and gender inequalities; the history of violence; and the transnational flows that have shaped the nation. "The Colombia Reader" expands readers' knowledge of Colombia beyond its reputation for violence, contrasting experiences of conflict with the stability and significance of cultural, intellectual, and economic life in this plural nation.